Perfection Is Not a Burden: A Gynocritical Study of Laksmi Pamuntjak's Blue Membrane Novel - Emilda Mayang Sari; Tristanti Apriyani (Raja Zulkarnain Education Foundation, 2026)
This study examines the construction of the perfect woman in Laksmi Pamuntjak's novel, Selaput Biru, through the perspective of Elaine Showalter's gynocriticism. The background of the study is based on the persistent strong cultural and social pressures on the ideal image of women in Indonesia, reflected in literary works and everyday life. The purpose of the study is to analyze how the novel, Selaput Biru, represents the perfect woman and to explore the renegotiation of this concept through the narratives of the main characters. This study is a qualitative descriptive study, using data sources in the form of phrases, words, and sentences in the novel, Selaput Biru. The data analysis technique used was content analysis, and to ensure data validity, the researcher used data triangulation. The results show that the representation of the perfect woman in the novel, Selaput Biru, emphasizes the importance of women's experiences, acknowledges complexity and imperfection, and resists patriarchal norms and social hierarchies. This study recommends further studies of women's narratives that respect the complexity and diversity of women's life experiences.